Negotiating Authority: Argumentative Techniques in Da’wah Narratives on Hijab - Maimunah; Prianto, Agung Teguh (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
The contemporary discourse on the hijab reflects not only religious norms but also ongoing debates among Islamic scholars regarding interpretation and authority. This study examines how leading preachers—Quraish Shihab, Ustaz Adi Hidayat, and Ustaz Wijayanto—construct arguments about hijab regulation, with a focus on their use of scriptural sources, authority methods, and contextual reasoning. Employing a comparative qualitative approach grounded in Stephen Toulmin’s model of argumentation, this research analyzes their public statements, sermons, and writings. The findings indicate significant methodological variance: Quraish Shihab adopts a contextual and adaptive approach, whereas Ustaz Adi Hidayat and Ustaz Wijayanto apply a literal and traditionalist method. Despite their differences, all three rely foremost on the Qur’an and Hadith as sources of religious authority. These approaches have tangible effects on Muslim practices and perceptions regarding the hijab. The study emphasizes that scholarly argumentation, grounded in credible sources and critical engagement, is crucial for fostering a pluralistic and constructive intellectual climate within contemporary Islamic discourse.